2022
DOI: 10.3390/jcm11174940
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated Vitrified Embryos Could Be a Method for Increasing Pregnancy Rates in Patients with Poor Ovarian Response

Abstract: We aimed to assess the efficacy of accumulated embryo transfer (ACC-ET) through several controlled ovarian hyperstimulation (COS) cycles to increase the rates of pregnancy in patients with poor ovarian response (POR). We retrospectively reviewed the medical records of 588 patients with POR under 43-years old who underwent embryo transfer from January 2010 to December 2015. We compared the pregnancy rate (PR), clinical pregnancy rate (CPR), and live birth rate (LBR) between ACC-ET (frozen-thawed: 47; fresh + fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The accumulation of embryos or oocytes from several stimulation cycles has also been suggested to enhance the possibility of childbirth in women with a limited ovarian reserve [55,56]. Referring to recent articles, there is a lack of evidence that the transfer of multiple embryos obtained from several cycles increases pregnancy rates in AMA patients [57]. Previous studies have highlighted that extended embryo culture until the blastocyst stage is the best way to select embryos with the highest implantation potential in patients with good ovarian reserve [58].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of embryos or oocytes from several stimulation cycles has also been suggested to enhance the possibility of childbirth in women with a limited ovarian reserve [55,56]. Referring to recent articles, there is a lack of evidence that the transfer of multiple embryos obtained from several cycles increases pregnancy rates in AMA patients [57]. Previous studies have highlighted that extended embryo culture until the blastocyst stage is the best way to select embryos with the highest implantation potential in patients with good ovarian reserve [58].…”
Section: Discussionmentioning
confidence: 99%
“…The results of ART for poor responders are improved by oocyte accumulation and embryo accumulation. Pregnancy rates might be raised by transferring enough embryos utilizing frozen, thawed embryo transfer (ET) and obtaining embryos from POR patients using numerous COS, natural, or modified natural procedures, as Jieun Shin et al showed in their retrospective analysis (24).…”
Section: Outcomes Of Art In Accumulation Cyclesmentioning
confidence: 99%